(3ZGjI GdMcjes - (3eSdeI Hf CMeO Hf bGSe Hf YHO Gddg GdeLQjWj, CHh GdbGSe,J (B398 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CTQbJ ef fhQg CeG HYO CjgG GdWGdH GdeZQi HGdNhV ai Yde GdadGSaI hGdfXQ ai CSQGQge s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3hGWHY GdTcd HGdefGSHI hWdH GdGROhGL GdPi gh ai gPg GdUfGYI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B234s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1191s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMQha h GdChaGbs